Characterization of surface topography during multi-pass WEDM of MWCNT alumina composites. (April 2023) - Singh, Meinam Annebushan; Sarma, Deba Kumar; Hanzel, Ondrej; Sajgalik, Pavol; Ramkumar, Janakarajan
Abstract: The thermal spalling action of material removal associated with electrical discharge machining of ceramics results in severe surface debris, cracks, pores, etc. This led to a rough machined surface, ultimately rendering the machined component not susceptible for direct applications. Such a behavior points towards the need to further process the machined surface so as to reduce the net severity of the machined surface. The current work utilizes multi-pass wire electrical discharge machining to enhance the machined surface characteristics of alumina composites. Detailed comparison of the surface characteristics with regards to amplitude, spatial, hybrid and functional volume parameters depicted a superior and homogenous machined surface post multi-pass process. The recast layer severity was minimal as well by incorporation of multi-pass. Furthermore, a detailed analysis of the structural fingerprints of the surface elements depicts actual breakage and subsequent burn-out of the filler material. Highlights: Successful reduction of the surface severities post multi pass WEDM process, leading to a very fine machined surface. Detailed surface characterization depicts reduction of peaks/valleys, paving way for high homogeneity of the machined surface. Spatial and hybrid surface analysis depicts consistent removal of the peaks and subsequent filling of the valleys/voids with multi pass. The porous network and the recast layer severity decreases considerably post multi pass due to subsequent filling and removal action.